Knowledge, attitude and practices of environmental health practitioners conducting food-borne disease outbreak investigation at a local municipality in Gauteng province, South Africa - Thokozani P. Mbonane; Nisha Naicker (AOSIS, 2020)
Background: Food-borne disease (FBD) outbreaks are a common occurrence that is either not investigated or poorly investigated. According to anecdote evidence, this is because of non-uniformity to environmental health practices in South Africa. Aim: This study aimed to determine and describe the knowledge, attitude and practices (KAP) of environmental health practitioners (EHPs) when conducting outbreak investigations of FBD at a local municipality. Setting: This study was conducted in three sub-districts of Ekurhuleni Metropolitan Municipality (EMM), one of five municipalities in Gauteng province, South Africa. Methods: A descriptive cross-sectional study was conducted to collect data using a semi-structured questionnaire. Data collected were analysed using IBM Statistical Package for the Social Sciences. Continuous variables were compared using analysis of variances, and correlation was used to determine any association. Results: Knowledge responses were scored out of 9. Open-ended questions were themed into five items (support, guidelines, resources, training and specialisation). Sixty-one (76.3%) participants were randomly selected to participate in the study. There were more female participants (55.7%) than male participants, and the mean age was 30.9 years. The participants' knowledge scores ranged from 1 to 9. There were 17 (27.9%) participants who have conducted FBD outbreak investigation. Twenty-six (42.6%) believed that they were properly trained to conduct FBD outbreak investigations. Age was associated with position (p = 0.000) and qualification (p = 0.033). Conclusion: The results indicated that there are gaps and challenges in the knowledge, while the practices were not consistent amongst environmental health practitioners. However, the attitude of EHPs was positive with regard to their role in FBD outbreak investigations.